The Native American contest powwow cultural tethering theory - Aicinena, Steven; Ziyanak, Sebahattin 1977- (Lexington Books, 2021)
"This book examines the contest powwow to better understand what it means to participants and how it carries on the beauty of Native American culture. The authors assess how competitive dancing aligns with and differs from traditional sports while introducing their concept of Cultural Tethering Theory to understand its importance"--